Evaluation of Operation and Maintenance Performance for The Community-based Drainage System in Pengambengan Bali - I Gusti Ngurah Putu Dharmayasa; Putu Indah Dianti Putri; Andry Dwi Wibowo; Irma Suryanti (Jurnal Ilmiah Dinamika Rekayasa, 2026)
Recurring inundation in the Jalan Raya Pengambengan area, Bali, indicates a decline in the drainage infrastructure's Level of Service (LoS), leading to road structure degradation. This functional failure is primarily driven by non-structural factors, specifically deficiencies in Operation and Maintenance (O&M) management due to high sedimentation rates and waste accumulation. This study aims to evaluate drainage management effectiveness using a quantitative approach with a correlational design. Data were collected through structured questionnaires from 30 respondents residing along the primary channel, supported by field observations of the channel's physical condition. Descriptive statistical analysis revealed a sharp disparity: the community possesses a very high understanding of infrastructure function (index 81.66%), yet actual maintenance participation remains low (index 59.83%). The Spearman Rank correlation test confirmed no significant linear relationship (rs​=−0,079) between technical literacy and maintenance behavior. These findings demonstrate a knowledge-behavior gap phenomenon, where the degradation of hydraulic capacity is caused by the diffusion of responsibility regarding public assets. The study concludes that restoring drainage function requires a strategic transformation from mere physical intervention to strengthened institutionalized participatory asset management to sustainably mitigate flood risks.